Control of the data-retention characteristics of ionic-liquid conducting-bridge memory by designing device structures based on corrosion mechanisms. (2nd August 2021) - Sato, Hiroshi; Shima, Hisashi; Honma, Yusei; Naitoh, Yasuhisa; Akinaga, Hiroyuki; Nokami, Toshiki; Itoh, Toshiyuki; Sato, Dan; Kinoshita, Kentaro
Abstract: We fabricated an ionic-liquid conductive-bridge memory (IL-CBRAM) in which the solid-state electrolyte in a conventional CBRAM sandwich structure of Cu- and Pt-electrodes was replaced with IL. To stabilize the Cu-filaments in IL, an additional metal layer with a standard electrode potential (SEP) lower than that of Cu was inserted into the memory cell. We found Ta to be promising for this purpose, because the SEP in IL exhibited the Ta < Cu < Pt relation. Actually, inserting the Ta-adhesion layer increased the data-retention time. The data-retention characteristics control through cell design considering the SEP arrangement of metals was successfully demonstrated.